SIPANDAI: Development of an Integrated Village Public Service Website Using the Agile Method - Alisa Zahra Syahdia; Alya Wulandari; Muh. Asdar; Andi Naufal Abiyyu Tsarwat (Academic Bright Collaboration, 2024)
The development of information technology has encouraged the transformation of public services in villages to be more efficient and transparent. This research aims to develop the Integrated Village Information and Service System (Sipandai) website to overcome administrative problems such as population data collection, correspondence, and access to information. Sipandai provides digital administration features, budget transparency, village news, and online levy payments. The system development uses the iterative and flexible Agile method, allowing for customization according to the user's needs. The results of the development show that the implementation of Agile supports the effectiveness of the system, improves the quality and speed of public services in the village, and encourages community participation in more transparent governance. Sipandai also functions as a means of community empowerment and strengthening information technology-based village governance. The test results using the Black Box and White Box methods showed a 100% success rate with no errors found in all test scenarios